Asuhan Keperawatan Medikal Bedah Dengan Penyakit Paru Obstruktif Kronis Diruang Paru RSUD Prof.H.Muhammmad.Yamin,SH - Nabila Sukma; Aulia Asman; Linda Marni; Kheniva Diah Anggita (CV. ITTC INDONESIA, 2026)
Smoking habits are the main factor causing Chronic Obstructive Pulmonary Disease (COPD), both in active smokers and individuals exposed to cigarette smoke. Continuous exposure to cigarette smoke can trigger chronic inflammation in lung tissue, leading to respiratory function disorders. According to the World Health Organization (WHO) in 2024, COPD ranked as the fourth leading cause of death worldwide, with approximately 3.52 million sufferers. At Prof. H. Muhammad Yamin, SH Regional General Hospital, COPD is included among the ten most common diseases and ranks tenth overall. The purpose of this paper is to describe the implementation of nursing care for patients with COPD. The sample was Mr. Y, who was treated from February 6–10, 2026. Data were collected through interviews with the patient and family, observations, physical examinations, and diagnostic reports. The nursing problems identified included ineffective airway clearance, ineffective breathing patterns, activity intolerance, sleep pattern disturbances, and knowledge deficits. Evaluation results showed that ineffective airway clearance was not resolved, while ineffective breathing patterns, activity intolerance, sleep pattern disturbances, and knowledge deficits were resolved. Therefore, patients and families are advised to continue post-COPD care through chest physiotherapy (clapping and vibration), effective coughing techniques, and drinking warm water to help thin secretions.